Sports dentistry intricacies with season-related challenges and the role of athlete-centered outcomes - Júdice, André; Botelho, João; Machado, Vanessa; Proença, Luís; Ferreira, Luciano M. A.; Fine, Peter; Mendes, José João (Frontiers in Oral Health, 2025)
Sports dentistry is an emerging field focusing on the prevention, treatment, and management of oral health issues in athletes. This review critically examines the current state of sports dentistry, emphasizing the integration of oral health care into athletes' overall health management. The high prevalence of dental caries, erosion, and periodontal problems among athletes is linked to diet, habits, and increased risk of orofacial injuries. Routine oral health evaluations, particularly during the preseason, are recommended to tailor prevention strategies and address potential issues early on. The recently proposed Universal Screening Protocol for Dental Examinations in Sports is discussed, noting its potential limitations in terms of time and complexity. The review explores the challenges posed by athletes' demanding training and competition schedules, stressing the importance of incorporating oral health care into the medical team. Future research should investigate the feasibility and validity of self-reported questionnaires for screening oral health conditions, potentially simplifying the process for athletes. The review highlights the use of athlete-reported outcomes and self-reporting in sports dentistry as crucial for evaluating dental care effectiveness and monitoring long-term health outcomes. It concludes by emphasizing the need for streamlined, universally applicable protocols that fit athletes' schedules while providing comprehensive care, and the importance of further research to explore innovative screening tools and self-reported measures to transform routine care practices and reduce barriers to dental health for athletes.